Peningkatan Pemahaman Pertanian Organik Melalui Pemanfaatan Limbah Kotoran Ayam Ras Pedaging (Broiler) Sebagai Pupuk Organik Padat di Desa Kawo Kabupaten Lombok Tengah - Ibrahim; Wuryantoro; Mandalika, Eka Nurminda Dewi; Ayu, Candra; Watoni, Nurtaji (Universitas Mataram, 2024)
The problem of broiler manure waste is something that is often faced by farmers in Kawo Village, Pujut District, so the purpose of this service activity is to utilize broiler manure waste as organic fertilizer through training in making solid organic fertilizer and providing an understanding of organic farming. This activity involved 15 chicken farmers. The method of implementing this activity includes the preparation and socialization stage, the extension stage (Submission of material), the training stage for making organic fertilizer, and the evaluation of activities through pre-test and post-test. The results of the activity showed that the participants' knowledge and skills about fertilizer and organic farming increased significantly. From the post-test results, 87% have understood the benefits of organic farming and the benefits of chicken manure as organic fertilizer and have successfully made their own organic fertilizer.